Influence of irrigation and placement of nitrogen fertilizers on the uptake of nitrogen by spring wheat - Kaila, Armi; Elonen, Paavo (Agricultural and Food Science, 1970)
The effect of irrigation and fertilizer placement on the accumulation of nitrogen in the aerial parts of spring wheat was studied in the relatively dry summer 1969, on the basis of plant samples collected at various stages of development from a field trial on silty clay soil. In addition to 16 kg/ha of nitrogen in the basal dressing, 120 kg/ha of nitrogen was applied as ammonium nitrate limestone, as urea, or as Ureaform, either on the surface, or in rows at the depth of 8 cm. 60 mm of water was applied by sprinkler irrigation, one half about three, and the other half about four weeks after sprouting. Under the conditions of this trial, spring wheat only slightly responded to Ureaform. No significant difference in the effect of urea and ammonium nitrate limestone could be detected. Placement of these two fertilizers tended to increase both the amount of dry matter and its content of nitrogen; these effects were more significant without irrigation. Though irrigation, usually, markedly increased the total amount of nitrogen in the aerial parts of the plants, this was in the later stages of development due only to higher yields of dry matter, since in July the positive effect of irrigation on the percentage of nitrogen in plant dry matter changed to a negative effect. In the grain yields the apparent recovery of nitrogen in urea or ammonium nitrate limestone was estimated to be only about 30 per cent of the 120 kg N/ha applied as surface dressing. Irrigation increased this recovery to 54 per cent, placement of the fertilizer to 42 per cent, and both placement and irrigation resulted in an apparent recovery of 61 per cent. On the basis of plant samples collected two days before harvest, the apparent recovery of nitrogen in urea or ammonium nitrate limestone by the aerial parts of wheat was estimated to be, on the average, 36 per cent from the surface-dressing, and 60 per cent when the fertilizers were placed. Irrigation increased the apparent recovery in the first case to 76 per cent and in the latter case to 96 per cent. Thus, in the field experiment the uptake of fertilizer nitrogen by spring wheat was markedly increased by irrigation and to a lesser extent by fertilizer placement. Both treatments together are recommended.